Building therapeutic relationship in schizophrenic and alcohol-related disorder cases. Issue 3 (2nd July 2016) - Andrisano-Ruggieri, Ruggero; Crescenzo, Pietro; Ambrosio, Rosa; Pinto, Gaetano; Grieco, Francesco
Abstract : Current literature on the dual diagnosis in cases of schizophrenia and alcohol dependence has reported how pharmacological treatment has positive effects on the reduction of both disorders. Nevertheless, patients have considerable difficulties in following the prescribed medication. This work aims to build an engagement stage and therapeutic relationship in seven patients with schizophrenic and alcohol-related disorder cases. This result was achieved through the use of the vignette technique and narrative psychodynamic approach during group counselling sessions. Positive and Negative Symptoms Scale (PANSS) and Munich Alcoholism Test (MALT) were applied before and after treatment. A follow-up session was organized. The PANSS and MALT scores indicated there was no reduction of the psychiatric symptoms after treatment. The follow-up session showed positive outcomes in terms of increasing the level of socialisation as well as awareness of their own condition; at the same, an adherence to pharmacological treatment and psychotherapy for all the subjects.